Analisis Bibliometrik Pemetaan Tafsir Jalalain - Fitri Andaryani (Gunung Djati Conference Series, 2023)
The Qur'an as a guide for human life, its truth is absolute and non-negotiable for every Muslim. To practice all the instructions of the Qur'an, such an obligation will not be carried out without first understanding the intentions contained therein. This study tries to answer the shortcomings of previous studies, namely regarding the Jalalain interpretation. This study uses a bibliometric approach by using mapping analysis keywords using bibliometrics. In the research category, the dominant Jalalain interpretation is researched in the field of Philosophy and the Study of Religions. Researchers are interested in studying the grammatical in writing the Jalalain interpretation, namely explaining the Jalalain interpretation comprehensively.